Challenges for Competence-Oriented Education in the Context of the Development of Artificial Intelligence systems - Rodica Milena Zaharia (Amfiteatru Economic)
The debates about the challenges launched to the educational process by Artificial Intelligence systems are more acute than ever. On one hand, education, in general, must be that process that ensures the skills that allow the creation of Artificial Intelligence. Algorithms, chatbots, learning machines were created as a result of knowledge, skills and abilities acquired through education. They will continue to be the result of the creativity, inventiveness and daring of those who are educated in this spirit, of those who are cultivated with these skills. “Working” with Artificial Intelligence systems also requires knowledge, skills and abilities that the entire educational system must provide. Operating with Artificial Intelligence systems needs not only specific skills, but also their permanent adaptation as Artificial Intelligence systems become more complex and more performant.